Educational Modeling Drives Company Value Creation - Raharjo, Dwi Sihono (Dinasti International Journal of Digital Business Management, 2023)
This study aims to explore the connection between education and the creation of value within corporations. Education, as a value-driving factor, is measured in terms of human resource development across two variables: training & development and cost control. Research reveals that these variables have a significant impact on employee performance, which in turn plays a role in driving financial performance. Combining non-financial and financial perspectives, this creates a leading-lagging continuum. The research method is quantitative, utilizing a purposive sampling technique and panel data analysis through E-views10. Results demonstrate that employee performance is positively linked to profitability, which is achieved through increased revenue and controlled costs. The impact of human resource factors on financial performance is highly significant, ranging between 81.74 percent and 100 percent with a p-value of < 0.05. Apart from gross profit, net profit, and NOPAT, economic value added (EVA) also generates a positive impact. EVA stands as a true gauge of profitability, a crucial element that determines the success of corporate operations. By precisely calculating the cost of capital employed, EVA provides accurate profit figures. Moreover, it is a decisive factor in determining a company's stock price, making it an essential tool in creating and boosting company value.